Team of Teams: New Rules of Engagement for a Complex World - McChrystal, General Stanley; Silverman, David; Collins, Tantum; Fussell, Chris (Portfolio Penguin, 2015)
As commander of Joint Special Operations Command (JSOC), General Stanley McChrystal discarded a century of management wisdom and pivoted from a pursuit of mechanical efficiency to organic adaptability. In this book, he shows how any organization can make the same transition to act like a team of teams - where small groups combine the freedom to experiment with a relentless drive to share their experience.Drawing on a wealth of evidence from his military career and sources as diverse as hospital emergency rooms and NASA's space program, McChrystal frames the existential challenge facing today's organizations, and presents a compelling, effective solution.

A Governance Practitioner’s Notebook: Alternative Ideas and Approaches - Whaites, Alan; Gonzalez, Eduardo; Fyson, Sara; Teskey, Graham (OECD, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Systems Thinking For Social Change: A Practical Guide to Solving Complex Problems, Avoiding Unintended Consequences, and Achieving Lasting Results - Stroh, David Peter (Chelsea Green Publishing, 2015)
Donors, leaders of nonprofits, and public policy makers usually have the best of intentions to serve society and improve social conditions. But often their solutions fall far short of what they want to accomplish and what is truly needed. Moreover, the answers they propose and fund often produce the opposite of what they want over time. We end up with temporary shelters that increase homelessness, drug busts that increase drug-related crime, or food aid that increases starvation. How do these unintended consequences come about and how can we avoid them? By applying conventional thinking to complex social problems, we often perpetuate the very problems we try so hard to solve, but it is possible to think differently, and get different results. Systems Thinking for Social Change enables readers to contribute more effectively to society by helping them understand what systems thinking is and why it is so important in their work. It also gives concrete guidance on how to incorporate systems thinking in problem solving, decision making, and strategic planning without becoming a technical expert. Systems thinking leader David Stroh walks readers through techniques he has used to help people improve their efforts to end homelessness, improve public health, strengthen education, design a system for early childhood development, protect child welfare, develop rural economies, facilitate the reentry of formerly incarcerated people into society, resolve identity-based conflicts, and more.  The result is a highly readable, effective guide to understanding systems and using that knowledge to get the results you want.

Navigating Complexity in International Development: Facilitating Sustainable Change at Scale - Burns, Danny; Worsley, Stuart (Practical Action Publishing, 2015)
Governments and organizations invest huge sums of money in development interventions to explicitly address poverty and its root causes. However, a high proportion of these do not work. This is because interventions are grounded in flawed assumptions about how change happens -- change is rarely linear, yet development interventions are almost entirely based on linear planning models. Change is also characterized by unintended consequences, which are not predictable by planners and by power dynamics, which drive outcomes towards vested interests rather than real need. Development processes need to engage effectively with these sorts of complex system dynamics. This book provides a conceptual framework for this thinking, offers detail case studies of interventions which have been built on this philosophy and which demonstrate key facets of it. It articulates some clear methodological underpinnings for this work, and draws out the implications both for development, practice and practitioners.
Keywords: IMPORTANT

Embracing Complexity: Strategic Perspectives for an Age of Turbulence - Boulton, Jean G.; Allen, Peter M.; Bowman, Cliff (Oxford University Press, 2015)
The book describes what it means to say the world is complex and explores what that means for managers, policy makers and individuals. The first part of the book is about the theory and ideas of complexity. This is explained in a way that is thorough but not mathematical. It compares differing approaches, and also provides a historical perspective, showing how such thinking has been around since the beginning of civilisation. It emphasises the difference between a complexity worldview and the dominant mechanical worldview that underpins much of current management practice. It defines the complexity worldview as recognising the world is interconnected, shaped by history and the particularities of context. The comparison of the differing approaches to modelling complexity is unique in its depth and accessibility. The second part of the book uses this lens of complexity to explore issues in the fields of management, strategy, economics, and international development. It also explores how to facilitate others to recognise the implications of adopting a complex rather than a mechanical worldview and suggests methods of research to explore systemic, path-dependent emergent aspects of situations. The authors of this book span both science and management, academia and practice, thus the explanations of science are authoritative and yet the examples of changing how you live and work in the world are real and accessible. The aim of the book is to bring alive what complexity is all about and to illustrate the importance of loosening the grip of a modernist worldview with its hope for prediction, certainty and control.

International Development - Illusions and Realities - Black, Maggie (New Internationalist, 2015)
Part of the popular, reissued NoNonsense series from New Internationalist'Development' is often misunderstood and can embrace everything from building a large dam to planting trees. The idea can often mask confusion, contradiction, deceit and corruption. This book is essential reading for anyone wanting to know what development actually is. It covers all the key themes and critically suggests ways to bring the poor and marginalised into the process.

Black Box Thinking: The Surprising Truth About Success - Syed, Matthew (Hachette UK, 2015)
The Sunday Times No.1 Bestseller From the Bestselling Author of BounceWhat links the Mercedes Formula One team with Google?What links Team Sky and the aviation industry?What connects James Dyson and David Beckham?They are all Black Box Thinkers.Black Box Thinking is a new approach to high performance, a means of finding an edge in a complex and fast-changing world. It is not just about sport, but has powerful implications for business and politics, as well as for parents and students. In other words, all of us.Drawing on a dizzying array of case studies and real-world examples, together with cutting-edge research on marginal gains, creativity and grit, Matthew Syed tells the inside story of how success really happens - and how we cannot grow unless we are prepared to learn from our mistakes.
Keywords: Psychology; Sports & Recreation / Sports Psychology; Strategic Planning

Dialogic Organization Development: The Theory and Practice of Transformational Change - Bushe, Gervase R. (EDS Publications Ltd., 2015)
Dialogic Organization Development is a compelling alternative to the classical action research approach to planned change. Organizations are seen as fluid,socially constructed realities that are continuously created through conversations and images change happens when those conversations and images change. Leaders and consultants can help foster, support, or accelerate the emergence of transformational possibilities by encouraging disruptions to taken-for-granted ways of thinking and acting and the use of generative images to stimulate new organizational conversations and narratives. Dialogic OD is a different mindset, but it s also the previously unrecognized underpinning of such diverse change methods as Appreciative Inquiry, the Art of Convening, Future Search, and many more.

The Politics of Evidence and Results in International Development: Playing the Game to Change the Rules? - Eyben, Rosalind; Guijt, Irene; Roche, Chris; Shutt, Cathy (Practical Action Publishing, 2015)
Understanding and demonstrating the effectiveness of efforts to improve the lives of those living in poverty is an essential part of international development practice. But who decides what counts as good or credible evidence? Can the drive to measure results do justice to and promote transformational change change that challenges the power relations that produce and reproduce inequality, injustice and the non-fulfillment of human rights? The Politics of Evidence in International Development provides a critical examination of the results agenda, with practical strategies for rendering it more helpful in supporting transformative development. The book deconstructs the origins and concepts of the results and evidence agendas employed in international development. It describes with concrete examples the current effects and consequences of the agenda, and goes on to outline a range of strategies used by individuals and organizations to resist, adapt or comply with the useful and problematic demands for results-oriented measurement and evidence of value for money."

Deliberation and Development: Rethinking the Role of Voice and Collective Action in Unequal Societies - Heller, Patrick; Rao, Vijayendra (World Bank Publications, 2015)
This book marries two fields that rarely converse with one another:deliberative democracy and development studies. The study ofdeliberation―which explores normative and practical questions aroundgroup-based decision making through discussion or debate―has emergedas a critical area of study over the past two decades. Concurrently, the fieldof development has seen a spurt of interest in community-led developmentand participation premised on the ability of groups to arrive at decisionsand manage resources via a process of discussion and debate. Despite thegrowing interest in both fields, they have rarely engaged with one another.This book, which brings together new essays by some of the leading scholarsin the field, deepens our understanding of participatory decision makingin developing countries while initiating a new field of study for scholarsof deliberation. In the process, it sheds light on how to best design andimplement policies to strengthen the role of participation in development.

Scrum For Dummies - Layton, Mark C. (John Wiley & Sons, 2015)
Practice an agile form of management to stop wasting time and money Scrum For Dummies is an easy to use guide to managing the tricky transition from a traditional project management methodology to the new and most popular agile framework. As the most efficient, successful methodology for team project management, Scrum relies on transparency, flexibility, and fluidity to deliver a final product that fulfills the needs of all stakeholders. Written in easy–to–read Dummies style, this book walks you through the core principles of Scrum and provides a roadmap for tangible implementation. The vast majority of projects go over budget, and billions of dollars are wasted every year on overruns. Put a stop to this wasteful leakage by switching to a management style that keeps all participants informed, up–to–date, and accountable. Authored by a Certified Scrum Trainer, Mark Layton, Scrum For Dummies covers the key ideas and processes behind Scrum methodologies, and presents the inner workings of the plan in an engaging and accessible format. Topics include: The Scrum values, roles, artifacts, and activities that make up the principle of this methodology When and how best to use Scrum The differences between Scrum and other agile methodologies Using Scrum for IT, finance, construction, health care, and more The book also delves into the everyday use of Scrum, and how it can help you achieve your own personal goals outside of work. There′s a reason why scrum is quickly becoming the standard approach to project management it works! If you want to stop wasting time and start producing more effectively, Scrum For Dummies is the guide that will get you there.

Why Greatness Cannot Be Planned: The Myth of the Objective - Stanley, Kenneth O.; Lehman, Joel (Springer, 2015)
Why does modern life revolve around objectives? From how science is funded, to improving how children are educated -- and nearly everything in-between -- our society has become obsessed with a seductive illusion: that greatness results from doggedly measuring improvement in the relentless pursuit of an ambitious goal. In Why Greatness Cannot Be Planned, Stanley and Lehman begin with a surprising scientific discovery in artificial intelligence that leads ultimately to the conclusion that the objective obsession has gone too far. They make the case that great achievement can't be bottled up into mechanical metrics; that innovation is not driven by narrowly focused heroic effort; and that we would be wiser (and the outcomes better) if instead we whole-heartedly embraced serendipitous discovery and playful creativity.Controversial at its heart, yet refreshingly provocative, this book challenges readers to consider life without a destination and discovery without a compass.

Experiential Learning: Experience as the Source of Learning and Development - Kolb, David (Pearson FT Press, 2015)

Understanding Indicators And Monitoring For Sustainability In The Context Of Complex Social-Ecological Systems - Haider, L. Jamila; Iribarrem, Alvaro; Gardner, Toby; Latawiec, Agnieszka E; Alves-Pinto, Helena; Strassburg, Bernardo (De Gruyter Open, 2015)

Digital lives in Ghana, Kenya and Uganda - Bailur, Savita; Donner, Jonathan; Locke, Chris; Schoemaker, Emrys; Smart, Charlotte (Caribou Digital, 2015)
Keywords: IMPORTANT

Cooperation Management for Practitioners: Managing Social Change With Capacity Works - GIZ (Springer Gabler, 2015)

Opening the black box: the contextual drivers of social accountability - Grandvoinnet, Helene; Aslam, Ghazia; Raha, Shomikho (New frontiers of social policy, 2015)
Keywords: Social accounting

The field guide to human-centered design: design kit - IDEO (IDEO, 2015)
Keywords: Design; IMPORTANT; Methode

Organizational Performance Index (OPI) Handbook: A practical guide to the OPI tool for practitioners and development professionals - Pact (Pact, 2015)
This handbook is intended to help development practitioners understand how to use and what can be achieved by Pact’s Organizational Performance Index (OPI) tool. This document will provide practitioners and managers with information on how the Pact OPI works and how best to incorporate it in their country strategy or program.

World Development Report 2015: Mind, Society, and Behavior - World Bank (The World Bank, 2015)
Development economics and policy are due for a redesign. In the past few decades, research from across the natural and social sciences has provided stunning insight into the way people think and make decisions. Whereas the first generation of development policy was based on the assumption that humans make decisions deliberatively and independently, and on the basis of consistent and self-interested preferences, recent research shows that decision making rarely proceeds this way. People think automatically: when deciding, they usually draw on what comes to mind effortlessly. People also think socially: social norms guide much of behavior, and many people prefer to cooperate as long as others are doing their share. And people think with mental models: what they perceive and how they interpret it depend on concepts and worldviews drawn from their societies and from shared histories.The World Development Report 2015 offers a concrete look at how these insights apply to development policy. It shows how a richer view of human behavior can help achieve development goals in many areas, including early childhood development, household finance, productivity, health, and climate change. It also shows how a more subtle view of human behavior provides new tools for interventions. Making even minor adjustments to a decision-making context, designing interventions based on an understanding of social preferences, and exposing individuals to new experiences and ways of thinking may enable people to improve their lives.The Report opens exciting new avenues for development work. It shows that poverty is not simply a state of material deprivation, but also a “tax” on cognitive resources that affects the quality of decision making. It emphasizes that all humans, including experts and policy makers, are subject to psychological and social influences on thinking, and that development organizations could benefit from procedures to improve their own deliberations and decision making. It demonstrates the need for more discovery, learning, and adaptation in policy design and implementation. The new approach to development economics has immense promise. Its scope of application is vast. This Report introduces an important new agenda for the development community.